1997
DOI: 10.1046/j.1365-2362.1997.1680723.x
|View full text |Cite
|
Sign up to set email alerts
|

Is the effect of acute hyperglycaemia on interdigestive antroduodenal motility and small‐bowel transit mediated by insulin?

Abstract: Acute hyperglycaemia inhibits antroduodenal motility. In non-diabetic subjects this inhibitory effect may result from reactive endogenous hyperinsulinaemia. Therefore, we investigated the effects of hyperinsulinaemia during both hyperglycaemia and euglycaemia on interdigestive antroduodenal motility (perfusion manometry) and duodenocaecal transit time (DCTT; lactulose breath-H2 test). Six healthy volunteers (age 20-26 years) were studied for 240 min on three separate occasions in random order during: (a) i.v. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
0

Year Published

1999
1999
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 27 publications
1
17
0
Order By: Relevance
“…We cannot exclude the possibility that serum insulin concentrations that are lower or higher than those evaluated may affect gastric emptying, or that the effects of insulin differ between normal subjects and patients with diabetes. Our observations, however, are consistent with the majority of previous studies that have evaluated the effects of insulin on gut motor function in normal subjects; in most cases in which an effect of insulin was evident, its magnitude was relatively small [20,39]. Furthermore, it has been shown that the effects of hyperglycaemia on gastric emptying, antral motility [1,15±17], gallbladder emptying [19] and anorectal motility [18] are related directly to the blood glucose concentration, e. g. postprandial antral motility is suppressed more at a blood glucose of 230 mg/dl (12.8 mmol/l) compared with 175 mg/dl (9.7 mmol/l) [16].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…We cannot exclude the possibility that serum insulin concentrations that are lower or higher than those evaluated may affect gastric emptying, or that the effects of insulin differ between normal subjects and patients with diabetes. Our observations, however, are consistent with the majority of previous studies that have evaluated the effects of insulin on gut motor function in normal subjects; in most cases in which an effect of insulin was evident, its magnitude was relatively small [20,39]. Furthermore, it has been shown that the effects of hyperglycaemia on gastric emptying, antral motility [1,15±17], gallbladder emptying [19] and anorectal motility [18] are related directly to the blood glucose concentration, e. g. postprandial antral motility is suppressed more at a blood glucose of 230 mg/dl (12.8 mmol/l) compared with 175 mg/dl (9.7 mmol/l) [16].…”
Section: Discussionsupporting
confidence: 91%
“…CCK and GLP-1 results in the Type I and Type II patients. In both the Type I and Type II patients the insulin infusion rate had no effect on serum concentrations of CCK or GLP-1 small intestinal transit by marked hyperglycaemia [11,12] is not replicated by hyperinsulinaemia [39] and, similarly, it has been reported that acute hyperglycaemia, but not secondary hyperinsulinaemia, blunts mechanoreceptor-mediated gastrocolonic responses [40], and the rectoanal inhibitory reflex [38].…”
Section: Discussionmentioning
confidence: 77%
“…[13]. It was shown that in healthy subjects hyperglycemia prolongs duodenocecal transit time [14], and that induced hyperglycemia has major inhibitory effects on postprandial small intestinal motility [15]. These mechanisms are likely to explain the retardation of small intestinal transit for solids and liquids during hyperglycemia.…”
Section: Discussionmentioning
confidence: 99%
“…He had not showngastroparetic symptoms such as nausea, vomiting or epigastric discomfort, which may indicate silent gastroparesis (12). Gastric hypomotility in diabetes mellitus is believed to be due to diabetic autonomic neuropathy (1,4) or acute blood glucose change (5,6). Gastric hypomotility is related to the degree of autonomic neuropathy, but not to peripheral neuropathy, actual blood glucose and HbAlc (4).…”
Section: Discussionmentioning
confidence: 99%
“…These upper gastrointestinal symptomshave been attributed to gastroparesis, which is also an important factor in causing unstable glycemic control in IDDMpatients due to the discrepancy between the onset of insulin action and release of nutrients into intestines (3). Diabetic gastroparesis is believed to result from gastric hypomotility due to diabetic autonomic neuropathy (1 , 4) or acute blood glucose change (hyperglycemia-hypoglycemia) (5,6). Acute gastric dilatation can be life-threatening due to hypovolemic shock resulting from impaired inferior vena cava return (7).…”
Section: Introductionmentioning
confidence: 99%